2010
DOI: 10.1371/journal.pone.0009849
|View full text |Cite
|
Sign up to set email alerts
|

Polo-Like Kinase 2-Dependent Phosphorylation of NPM/B23 on Serine 4 Triggers Centriole Duplication

Abstract: Duplication of the centrosome is well controlled during faithful cell division while deregulation of this process leads to supernumary centrosomes, chromosome missegregation and aneuploidy, a hallmark of many cancer cells. We previously reported that Polo-like kinase 2 (Plk2) is activated near the G1/S phase transition, and regulates the reproduction of centrosomes. In search for Plk2 interacting proteins we have identified NPM/B23 (Nucleophosmin) as a novel Plk2 binding partner. We find that Plk2 and NPM/B23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…3). Table 2 shows the selected list of TBK1-PLK1 subnetwork components, which revealed that TBK1 knockdown leads to decreased activating phosphorylation of PLK1 (Thr-210) and its mitotic target proteins (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These results prompted us to validate our idea that TBK1 is involved in mitotic regulation through activating PLK1.…”
Section: Resultsmentioning
confidence: 70%
“…3). Table 2 shows the selected list of TBK1-PLK1 subnetwork components, which revealed that TBK1 knockdown leads to decreased activating phosphorylation of PLK1 (Thr-210) and its mitotic target proteins (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These results prompted us to validate our idea that TBK1 is involved in mitotic regulation through activating PLK1.…”
Section: Resultsmentioning
confidence: 70%
“…During mitosis, NPM is mainly dispersed throughout the cell with a minor fraction located at the spindle poles and its phosphorylation is required for this localization (Yao et al, 2004;Negi and Olson, 2006). Several sites are phosphorylated in mitosis: S4 by polo-like kinase 1 (but also in S-phase by Plk2 (Krause and Hoffmann, 2010)), and S70 and S254 by unknown kinases (Nousiainen et al, 2006). Moreover, NPM is a target of the NimA-like protein kinase (Nek2A), although the phosphorylation sites have not been mapped (Yao et al, 2004).…”
Section: Regulation Of Npm Activities Through Post-translational Modimentioning
confidence: 99%
“…Polo-like kinase 2 (Plk2) is also involved in the regulation of centriole reproduction (Warnke et al, 2004). It is known that Plk2 phosphorylates NPM/B23 to trigger centriole duplication and CPAP to control its biological activity for centriole elongation (Chang et al, 2010;Krause and Hoffmann, 2010).…”
Section: Introductionmentioning
confidence: 99%